A prospective clinical study comparing the use of conventional electrocautery and harmonic scalpel for hemorrhoidectomy - Gupta, Shweta B.; Mitra, Arti S. (International Surgery Journal, 2025)
Background: Haemorrhoids are a common ailment affecting the adult population with hemorrhoidectomy being the standard of care for 3 and 4 haemorrhoids. The purpose of this study was to analyze and compare outcomes between hemorrhoidectomy performed with Harmonic Scalpel vs electrocautery. Methods: A total of 46 patients admitted in our institute from August 2022 to September 2024 with grade 3 and 4 haemorrhoids were included in the study. Both arms of study had 23 patients each with one arm undergoing hemorrhoidectomy using Harmonic Scalpel and the other using electrocautery. Results: There was no significant difference observed in operating time. Significantly lower intra as well as post operative bleeding was recorded with Harmonic Scalpel. Post operative pain using VAS scale at 12, 24 and 48 hours was significantly lower in Harmonic Scalpel group. Also the need for post operative analgesia was lower in Harmonic Scalpel group. All above findings contributed to lower hospital stay in Harmonic Scalpel group. Conclusions: We conclude that , Harmonic Scalpel hemorrhoidectomy is safer, better and is associated with less intra as well as post operative bleeding , decreased pain scores with less analgesia requirement along with reduced hospital stay as compared to electrocautery hemorrhoidectomy.